Wide-Field Fluorescein Angiography in Wet Age-Related Macular Degeneration. (14th October 2014) - Madhusudhan, Savitha; Beare, Nicholas
Abstract : Purpose . The aim of our study was to investigate if peripheral retinal ischaemia contributed to the pathogenesis of neovascular AMD (NvAMD), using wide-field fluorescein angiography (WFFA). Methods . This prospective study included 30 consecutive patients with newly diagnosed NvAMD in the index eye. Wide-field colour fundus images and fluorescein angiograms were obtained using P200C optomap FA and analysed using a grid with three concentric circles of 50°, 100°, and 200° centred on the fovea to define zones Z1, Z2, and Z3. Results . Areas of peripheral retinal nonperfusion were seen in 2 (7%) eyes, peripheral vascular leakage in 5 (17%) eyes, and diffuse dye leakage close to the ora in 5 (17%) eyes. A total of one-third of the study eyes showed changes on WFFA in Z2 and Z3. On comparing index eyes to nonindex eyes in these patients, the presence of NvAMD was associated with peripheral FA changes (P = 0.009, Fisher's test). Conclusion . Frank peripheral retinal non-perfusion does not appear to be associated with NvAMD. In some patients with active NvAMD there is degradation of the peripheral blood-retina barrier. Smoking was also found to be associated with the above-mentioned abnormalities.